The Effectiveness Of Using The Mondly Application In Developing Speaking Skills And Improving The Arabic Vocabulary Of Class Vii Students At Mts Al-Abrar Bulukumba - Khalik, Muh. Fihris; Musytari, Lu’lu Al-Maknun (MSJ : Majority Science Journal, 2024)
This study aims to determine the effectiveness of using the Mondly application in developing speaking skills and increasing Arabic vocabulary of VII grade students of MTs Al-Abrar Bulukumba. The methodology used is experimental research with a descriptive quantitative approach. The research design used was intact group comparison, where the experimental group was given special treatment. The research sample was seventh grade students at MTs Al-Abrar Bulukumba.The results showed that the use of Mondly application is effective in learning Arabic. Specifically, this application proved to be able to develop speaking skills and improve students' mastery of Arabic vocabulary. The findings suggest that learning technology, such as the Mondly app, can be a useful tool in the teaching and learning process of foreign languages, particularly Arabic, in the school environment.